How can the productivity of Indonesian cocoa farms be increased? - Andras Tothmihaly; Verina Ingram (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
This study investigates the Indonesian cocoa production to reveal the possibilities for poverty alleviation while considering the threats to environmental sustainability. We estimate, based on a large household panel data set and stochastic frontier analysis, the technical efficiency of cocoa production and decompose productivity growth. According to our results, the productivity of Indonesian cocoa farming increased by 75 percent between 2001 and 2013. Technical efficiency growth and the increased chemicals use supported by government subsidies were responsible for the majority of this gain. Furthermore, we find large distortions in the input allocations. Hence, policies that encourage the adjustment of the cocoa farms' input use would be highly beneficial. Moreover, because of the weather-induced volatility in cocoa production, policy makers should also promote investment in agricultural research and transfer of drought-resistant cocoa varieties to farmers. Additionally, the average efficiency of cocoa farmers is estimated to be around 50 percent. We find that farmers' educational attainment and their experience in cocoa farming are significant factors that can increase the efficiency levels.
Keywords: D24; O13; Q01; Q12; 330; cocoa; Indonesia; productivity change decomposition; technical efficiency